Evaluation of clinical abdominal scoring system for predicting outcomes of blunt abdominal trauma - Nico Odolf Yordanius; I Ketut Wiargitha; Nyoman Golden; I Wayan Periadijaya; I Wayan Sudarsa; I Wayan Niryana (Universa Medicina, 2023)
Background Trauma has been called the neglected disease of modern society and the most common cause of death under 45 years. Determining the optimal prospective course of action may be aided by the adoption of a scoring system to evaluate urgent laparotomy intervention. A quick and easy technique to identify whether there are any intra-abdominal injuries is to use the clinical abdominal scoring system (CASS). The objective of this study was to evaluate CASS in predicting the outcomes in patients with blunt abdominal trauma (BAT).